1997
DOI: 10.1002/(sici)1096-9861(19971110)388:1<146::aid-cne10>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Localization of dopamine D1 receptors and dopaminoceptive neurons in the chick forebrain

Abstract: The distributions of dopamine D1 receptors, dopaminoceptive neurons, and catecholaminergic fibers were investigated in the forebrain of the domestic chick by using D1 receptor autoradiography and immunohistochemical detection of D1 receptor protein (D1rp), the dopamine- and cAMP-regulated phosphoprotein DARPP-32, and tyrosine hydroxylase (TH). Particular attention was paid to two forebrain regions, the mediorostral neostriatum/ hyperstriatum ventrale (MNH) and neostriatum dorsocaudale (Ndc), which have been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
46
0
4

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 93 publications
(193 reference statements)
10
46
0
4
Order By: Relevance
“…Although Karten and Dubbeldam (1973) thought that its position resembled that of the mammalian internal pallidal segment, subsequent immunolabeling studies showed that it lacked the pallidal-type neurons and the SP/DYNcontaining striatal input characteristic of the internal pallidal segment Reiner and Carraway, 1987;Anderson and Reiner, 1990;Veenman and Reiner, 1994). More recent studies have shown that the INP contains spiny neurons that express DARPP32, a striatal characteristic (Schnabel et al, 1997;Reiner et al, 1998b), a very similar glutamate receptor profile to the striatum (Wada et al, 2001), and numerous cholinergic neurons , which is characteristic of, but not unique to, the striatum. Moreover, the INP has recently been found to develop within the striatal sector of the subpallium, to show continuity with the medial striatum, and to contain neurons expressing cell-surface proteins characteristic of striatal neurons .…”
Section: Intrapeduncular Nucleus (Inp) 3 Intrapeduncular Nucleus (Inp)mentioning
confidence: 99%
“…Although Karten and Dubbeldam (1973) thought that its position resembled that of the mammalian internal pallidal segment, subsequent immunolabeling studies showed that it lacked the pallidal-type neurons and the SP/DYNcontaining striatal input characteristic of the internal pallidal segment Reiner and Carraway, 1987;Anderson and Reiner, 1990;Veenman and Reiner, 1994). More recent studies have shown that the INP contains spiny neurons that express DARPP32, a striatal characteristic (Schnabel et al, 1997;Reiner et al, 1998b), a very similar glutamate receptor profile to the striatum (Wada et al, 2001), and numerous cholinergic neurons , which is characteristic of, but not unique to, the striatum. Moreover, the INP has recently been found to develop within the striatal sector of the subpallium, to show continuity with the medial striatum, and to contain neurons expressing cell-surface proteins characteristic of striatal neurons .…”
Section: Intrapeduncular Nucleus (Inp) 3 Intrapeduncular Nucleus (Inp)mentioning
confidence: 99%
“…This conclusion rests on a large data set involving neuroanatomical, physiological, neurochemical, and behavioral results. Neuroanatomical studies showed the NCL to receive multimodal input from all secondary sensory areas of the forebrain (Leutgeb, Husband, Riters, Shimizu, & Bingman, 1996), to project to telencephalic motor output structures as well as to the basal ganglia (Kröner and Güntürkün, 1999), to be innervated by dopaminergic fibers from midbrain cell groups A8 -A10 (Metzger, Jiang, Wang, & Braun, 1996), and to be characterized by a high density of dopamine D 1 receptors (Schnabel et al, 1997). Physiological studies demonstrated that single units in the NCL code for the upcoming reward (Kalt, Diekamp, & Güntürkün, 1999), bridge the delay between stimulus and response by high sustained activity levels (Diekamp, Kalt, & Güntürkün, 2002), and code for the subjective reward value of a reinforcer (Kalenscher et al, 2005).…”
mentioning
confidence: 99%
“…3), incluindo receptores de neurotransmissores, canais e bombas iônicas, além de fatores transcripcionais GREENGARD, 2001;SVENNINGSSON et al, 2004). A distribuição da DARPP-32 foi estudada através de técnicas de imunohistoquímica no cérebro de ratos (OUIMET e GREENGARD, 1990a, b), primatas (BERGER et al, 1990;OUIMET et al, 1992), e aves (SCHNABEL et al, 1997). Em todas as espécies examinadas, a DARPP-32 foi demonstrada estar enriquecida nas regiões do cérebro que receberam densas aferências dopaminérgicas e em particular em regiões contendo receptores do tipo D1.…”
Section: Darpp-32unclassified